e regulation of image and voice, two relevant legal aspects of The human person within the peruvian civil code in the time of Covid 19 - Balarezo Reyes, Emilio José (2020)
The treatment that the Peruvian legal system has conferred on image and voice is an essential knowledge of society, for which reason an analysis of the entire evolutionary process, both historical and legal, is carried out regarding their legal relevance, from the point of view of the main national regulatory bodies such as the Political Constitution of Peru, the Civil Code of 1984 and the Civil Procedural Code, as well as an examination of national doctrine as a foreign one regarding its treatment in the field of national law and comparative law.